Adsorption of Cu2+ on coal fly ash modified with functionalized mesoporous silica. (15th September 2015) - Pizarro, Jaime; Castillo, Ximena; Jara, Sebastián; Ortiz, Claudia; Navarro, Patricio; Cid, Héctor; Rioseco, Héctor; Barros, Daniel; Belzile, Nelson
Highlights: The waste material coal fly ash can be combined to a mesoporous material to adsorb metals. The synthesized compound is very efficient to remove Cu 2+ ions from contaminated waters. The best conditions for the adsorption of Cu 2+ have been investigated. Abstract: The surface properties of coal fly ash modified with a mesoporous siliceous material and functionalized with 3-aminopropyl-triethoxysilane were studied to evaluate the adsorption capacity of the new matrix for Cu 2+ ions under different pH, initial metal concentrations, number of contacts and times for different adsorbent masses. The synthesized material was characterized chemically and morphologically, showing an increase of active surface and pore uniformity with respect to the initial fly ash. The new material showed great affinity for Cu 2+, whose removal was between 98% in the 10–20 mg L −1 initial concentration range, and 95% removal in the 30–45 mg L −1 initial range. At pH > 4, there was an increased adsorption capacity of the matrix, with pH 5 being the optimum working condition. The Freundlich model is the one that best represents the adsorption capacity of the studied matrix.